2014
DOI: 10.1186/s13045-014-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Notch1-induced T cell leukemia can be potentiated by microenvironmental cues in the spleen

Abstract: BackgroundLeukemia is a systemic malignancy originated from hematopoietic cells. The extracellular environment has great impacts on the survival, proliferation and dissemination of leukemia cells. The spleen is an important organ for extramedullary hematopoiesis and a common infiltration site in lymphoid malignancies. Splenomegaly, frequently observed in T cell acute lymphoblastic leukemia (T-ALL), is associated with poor prognosis. However, how the spleen microenvironment distinctly affects T-ALL cells as opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
0
42
0
1
Order By: Relevance
“…The development of leukemia in vivo is governed by numerous intrinsic and microenvironmental factors. We previously demon- strated that Notch1-induced T-ALL could be potentiated by microenvironmental cues in the spleen (46). We did not observe any significant splenomegaly in clodronate liposomes-treated mice, which indicated that LAMs had effects on the development of leukemia in vivo.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The development of leukemia in vivo is governed by numerous intrinsic and microenvironmental factors. We previously demon- strated that Notch1-induced T-ALL could be potentiated by microenvironmental cues in the spleen (46). We did not observe any significant splenomegaly in clodronate liposomes-treated mice, which indicated that LAMs had effects on the development of leukemia in vivo.…”
Section: Discussionmentioning
confidence: 56%
“…We reported previously that the spleen microenvironment stimulated the proliferation and dissemination of Notch1-induced leukemia cells more potently than did the BM microenvironment. MIP-3b, which was higher in the spleen microenvironment than in the BM microenvironment, accounted for the greater potential to recruit T-ALL cells (46). We observed that spleen LAMs stimulated the proliferation of T-ALL cells more strongly, which suggested that they might play an important role in the spleen microenvironment to promote the development of T-ALL.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, the leukemic spleen was also able to promote leukemic cell homing and proliferation in comparison with leukemic BM. 33 In addition, the potentially increased inflammatory cytokines cannot explain the increased number of quiescent HSCs during leukemia development, despite the fact that previous reports have demonstrated an increased cycling fraction of HSCs under infection stress. 34,35 Our future studies will focus on (1) the extrinsic effects of leukemia on normal HSCs, including the alterations in cytokines and niche cells in leukemic BM, (2) how cytokine or niche cells regulate Egr3 expression in HSCs, and (3) the relationship between Egr3 and cell cycle regulatory genes.…”
Section: Discussionmentioning
confidence: 98%
“…We used a non-irradiated Notch1-induced mouse T-ALL model that was described previously 13,21 . C57BL/6J mice served as the control.…”
Section: Leukemia Mouse Modelmentioning
confidence: 99%